Something isn't right: The subtle changes of early deterioration. Issue 1 (January 2017) - Crowe, Sarah; Ewart, Lisa; Derman, Sarah
Abstract : Using a systems approach to assessment can help you identify common signs and symptoms of a patient's deteriorating condition, leading to appropriate care and improved outcomes.